Increased water content in bacterial cellulose synthesized under rotating magnetic fields. (3rd April 2017) - Fijałkowski, Karol; Żywicka, Anna; Drozd, Radosław; Junka, Adam Feliks; Peitler, Dorota; Kordas, Marian; Konopacki, Maciej; Szymczyk, Patrycja; Rakoczy, Rafał
ABSTRACT: The current study describes properties of bacterial cellulose (BC) obtained from Komagataeibacter xylinus cultures exposed to the rotating magnetic field (RMF) of 50 Hz frequency and magnetic induction of 34 mT for controlled time during 6 days of cultivation. The experiments were carried out in the customized RMF exposure system adapted for biological studies. The obtained BC displayed an altered micro-structure, degree of porosity, and water-related parameters in comparison to the non-treated, control BC samples. The observed effects were correlated to the duration and the time of magnetic exposure during K. xylinus cultivation. The most preferred properties in terms of water-related properties were found for BC obtained in the setting, where RMF generator was switched off for the first 72 h of cultivation and switched on for the next 72 h. The described method of BC synthesis may be of special interest for the production of absorbent, antimicrobial-soaked dressings and carrier supports for the immobilization of microorganisms and proteins.